Generation of a Bartter syndrome type 3 patient-derived induced pluripotent stem cell line ISRM-BS3-UM18-iPSC (HHUUKDi014-A) - Chantelle Thimm; Chutong Zhong; Wasco Wruck; Alessandra Grillo; Rosanne Mack; Martina Bohndorf; Nina Graffmann; Anson Tang; Viola D’Ambrosio; Elizabeth R Wan; Keith Siew; Rhys D Evans; et al. (Stem Cell Research, 2025)
SIX2-positive urine-derived renal progenitor cells (UdRPCs) were isolated from an 18-year-old Bartter syndrome type 3 (BS3) patient within a homozygous CLCNKB gene deletion. Two episomal-based plasmids expressing OCT4, SOX2, NANOG, KLF4, c-MYC and LIN28 we were able to generate an integration-free induced pluripotent stem cell line (iPSC). Pluripotency was confirmed by fluorescence-activated cell sorting analysis and immunocytochemistry for the markers-OCT4, SOX2, NANOG, TRA-1-60, TRA-1-81 and SSEA4. Embryoid body-based differentiation into the three germ layers was the conducted and confirmed by immunocytochemistry. Pluritest analysis revealed a Pearson correlation of 0,93. Short tandem repeat DNA fingerprinting and karyotype analyses were performed.